2019
DOI: 10.1021/acsbiomaterials.8b01425
|View full text |Cite
|
Sign up to set email alerts
|

Nano Textured PEEK Surface for Enhanced Osseointegration

Abstract: Polyetheretherketone (PEEK) is widely used in orthopedic and dental applications because of its similar mechanical properties to those of natural bones. However, the inferior osseointegration and bioinertness hamper the clinic application. The surface texture of biomaterials plays an essential role in controlling cell differentiation through affecting the cell-generated physical forces, thus improving the osseointegration of the substrate. In this work, argon PIII and subsequently hydrogen peroxide treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…To generate nanotopographies, magnesium metal is more suitable for surface modification with alkali solution [ 88 ]. For PEEK, nanosturctures can be prepared by argon plasma immersion implantation and hydrogen peroxide treatment [ 89 ]. The etching action by concentrated sulfuric acid on PEEK can generate a porous network structure [ 90 ].…”
Section: Effect Of Implant Surface Nanotopographies On Macrophages An...mentioning
confidence: 99%
“…To generate nanotopographies, magnesium metal is more suitable for surface modification with alkali solution [ 88 ]. For PEEK, nanosturctures can be prepared by argon plasma immersion implantation and hydrogen peroxide treatment [ 89 ]. The etching action by concentrated sulfuric acid on PEEK can generate a porous network structure [ 90 ].…”
Section: Effect Of Implant Surface Nanotopographies On Macrophages An...mentioning
confidence: 99%
“…In recent years, advances in nanotechnology have promoted novel strategies to increase the bioactivity of PEEK through modification of surface composition and/or morphology, aiming at obtaining implants with antibacterial properties, osteoconduction and improved mechanical strength [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In particular, modifications of surface micro- and nanotexture can control cell differentiation via affecting cell-generated physical forces, thus improving substrate osseointegration [ 21 ]. Methods to modify the PEEK surface mainly include plasma-immersion processes to reach the desired topological structures, with positive effects on cell–substrate interactions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the mechanical property of PEEK, the elastic modulus of PEEK is similar to that of cortical bone, which can effectively avoid bone non-union caused by stress shielding. Till now, numerous in vitro studies have confirmed the low cytotoxicity of PEEK to various cells[ 24 , 25 ]. After long-term implantation in the body, it will not release toxic and harmful ions in the follow-up period[ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%